Does Internal Security Expenditure Impact on Economic Growth in Nigeria? Array - Mbah, Stella Ada; Agu, Osmond Chigozie; Aneke, Chijioke E. (Acta Universitatis Danubius. Œconomica, 2021)
Any resource channeled into security has a trade-off effect, as it denies other sectors of the economy the needed resources that could be employed to enhance economic growth and welfare of the citizenry. This study examined the possible impacts of internal security expenditure on economic growth in Nigeria. Employing Autoregressive Distributed Lag (ARDL) estimating technique, the study estimated both the short-run and the long-run interactions between the chosen variables. The estimated result found internal security to be positively and significantly related to economic growth in the short-run but exhibits a negative and significant relationship with economic growth in the long-run. The result also revealed a negative and significant relationship between foreign direct investment and economic growth. Finally, the test for structural breaks found evidence for five breakpoints which interestingly corresponded with the periods of some structural and government policy changes in Nigeria. It is therefore recommended that resources to be channeled on security should be considered cautiously as not to adversely affect economic growth. Secondly, government should employ robust policies that would encourage foreign investments into the economy.